2007
DOI: 10.2106/jbjs.g.00082
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Repair of Traumatic Combined Rotator Cuff Tears Involving the Subscapularis Tendon

Abstract: Arthroscopic repair with use of the suture anchor technique is a safe and effective procedure for the treatment of combined rotator cuff tears involving the subscapularis tendon; it can alleviate shoulder pain and improve function and the range of motion. The postoperative integrity of the repair correlates with the clinical results. Patient age and the degree of tendon retraction can affect the integrity of the repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 40 publications
4
73
1
2
Order By: Relevance
“…19 A previous anatomic study of the subscapularis footprint indicated that the tendon portion occupied the superior two-thirds of the attachment, and the muscular portion occupied the inferior one-third. 18 These anatomic findings were used to grade tears of the superior one-third (the superior half of the tendon portion) as grade 1 and the superior two-thirds of the attachment (the entire tendon portion) as grade 2; tears affecting all tendon and muscle portions were recorded as grade 3.…”
Section: Classification Of Subscapularis Tearsmentioning
confidence: 97%
See 3 more Smart Citations
“…19 A previous anatomic study of the subscapularis footprint indicated that the tendon portion occupied the superior two-thirds of the attachment, and the muscular portion occupied the inferior one-third. 18 These anatomic findings were used to grade tears of the superior one-third (the superior half of the tendon portion) as grade 1 and the superior two-thirds of the attachment (the entire tendon portion) as grade 2; tears affecting all tendon and muscle portions were recorded as grade 3.…”
Section: Classification Of Subscapularis Tearsmentioning
confidence: 97%
“…Manual muscle strength, Neer and Hawkins impingement, supraspinatus, 20 infraspinatus, 12 liftoff, 9,19 belly-press, 9,19 and Speed tests were performed. All patients were evaluated at the latest follow-up by an orthopedic surgeon other than the primary surgeon.…”
Section: Physical Examinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although others have proposed an alternative pathoanatomy for this arthroscopic finding, the reduction of the tissue that represents the comma tissue to the remnant subscapularis has been shown to recreate the intraarticular aspect of the torn subscapularis while concurrently reducing the leading edge of the supraspinatus [85]. Short-term and long-term results of isolated subscapularis and combined rotator cuff tears involving the subscapularis have consistently been shown to lead to good or excellent results in the vast majority of cases, with structurally intact repairs evaluated via ultrasound and magnetic resonance imaging reported as high as 93% [86][87][88][89][90][91][92]. Additionally, the reduction of the comma tissue to the torn subscapularis tendon can help reduce the leading edge of supraspinatus tears when found concomitantly.…”
Section: Subscapularis Tears and "Comma" Tissuementioning
confidence: 99%